Genotypic Prevalence of KELL1/KELL2 and KELL3/ KELL4 Blood Group Antigens in Individuals from Four Cities of Punjab, Pakistan - Kausar, Tasleem; Noureen, Shumaila; Malik, Maham; Talib, Saima; Tariq, Nabila (BioScientific Review, 2022)
Kell blood group system (KBGS) plays a vital role in transfusion medicine and bears a multidimensional character. Kell antigens are very reactive and vital responses can be observed in case of mismatched blood. This research is aimed to check the frequency and prevalence of different antibodies (KELL1, KELL2, KELL3, and KELL4) of the KEL gene in the local population of four different cities of Punjab, Pakistan. To this end, two hundred volunteers (from different ethnic groups) were enrolled for blood sampling. A questionnaire was designed to collect the required demographic information covering gender, age, cast, blood group, and city of origin of all the participants. Genomic DNA was extracted using the phenol-chloroform method and DNA was quantified using a UV spectrophotometer. Screening for the two known variants (C578T, T193M) in exon 6 of KELL1/KELL2 and for another two variants (C841T, R281W) in exon 8 of KELL3/KELL4 was performed by using tetra arms PCR. Data was entered in the SPSS software. The frequency of contributing factors was calculated, followed by cross-tabulation and chi-square analysis. The results showed that the incidence of KELL2 was 90%, while KELL1 was observed only in 7.5% of samples and the heterozygous allele KELL1/KELL2 was reported in only 2.5% of the total samples, respectively. Similarly, the frequency of wild-type allele KELL3 was 2.5% and of mutant allele KELL4 it was 96%, while the frequency of heterozygous allele KELL3/KELL4 was 1.5%, respectively. Chi-square values of cast and the city of origin showed non-significant results for both variants, although the type of blood group was found to have a significant association with KELL3/KELL4 genotype. Our results are in line with the previously reported results of prior studies.